In vitro study of the antioxidative and antiproliferative capabilities of Lactobacillus casei 16‐fermented soymilk. Issue 1 (11th December 2019) - Qian, Fang; Zhang, Jiang; Hou, Kairong; Zhang, Yuqing; Wang, Zifei; Luo, Pengjie; Tuo, Yanfeng
Abstract: In this study, soymilk was fermented with Lactobacillus casei 16. The contents of aglycone isoflavones, saponins, total phenolic, and free amino acid in the fermented soymilk, and the protection for the HepG2 cells against 2, 2'‐azobis(2‐amidinopropane) dihydrochloride (ABAP) damage and the antiproliferative effects of the fermented soymilk on the HT‐29 cells and Caco‐2 cells were studied. The results showed that the levels of total phenolic, aglycone isoflavones, and free amino acids in the L. casei 16‐fermented soymilk were enhanced. The ethanol extract and the water extract of the L. casei 16‐fermented soymilk showed protection for HepG2 cells against ABAP damage and inhibited the proliferation of the HT‐29 cells and Caco‐2 cells, which may be attributed to the enhanced level of total phenolic, aglycone isoflavones, and free amino acids in the L. casei 16‐fermented soymilk. Abstract : Soymilk fermented with Lactobacillus casei 16 showed the enhanced levels of total phenolic, aglycone isoflavones, and free amino acids. L. casei 16 fermented soymilk showed protection for HepG2 cells against ABAP damage and inhibited the proliferation of human colon cancer cells, which may be attributed to the enhanced level of total phenolic, aglycone isoflavones, and free amino acids in the L. casei 16‐fermented soymilk.